2020
DOI: 10.1186/s12931-020-01439-4
|View full text |Cite
|
Sign up to set email alerts
|

The need for fast-track, high-quality and low-cost studies about the role of the BCG vaccine in the fight against COVID-19

Abstract: Bacillus Calmette-Guérin (BCG) vaccination is routine and near-universal in many low- and middle-income countries (LMIC). It has been suggested that BCG can have a protective effect on COVID-19 morbidity and mortality. This commentary discusses the limitations of the evidence around BCG and COVID-19. We argue that higher-quality evidence is necessary to understand the protective effect of the BCG vaccine from existing, secondary data, while we await results from clinical trials currently conducted in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…The vaccine enhanced production of pro-inflammatory cytokines, such as IL-1β, tumor necrosis factor, and IL-6 [ 21 ]. However, the role of BCG against COVID-19 remains unclear and requires further experiments and clinical trials [ 22 ]. A cohort study found no difference in SARS-CoV-2 infection rates among BCG-vaccinated versus unvaccinated adults [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine enhanced production of pro-inflammatory cytokines, such as IL-1β, tumor necrosis factor, and IL-6 [ 21 ]. However, the role of BCG against COVID-19 remains unclear and requires further experiments and clinical trials [ 22 ]. A cohort study found no difference in SARS-CoV-2 infection rates among BCG-vaccinated versus unvaccinated adults [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…BCG vaccine has a very safe track record in comparison to other vaccines. Several studies in countries with a rigorous BCG vaccination program have shown a significant correlation between BCG vaccination and decreasing COVID‐19 morbidity and mortality 22–24,70–73 . A recent retrospective cohort study confirmed that BCG vaccination is safe, not associated with hyperinflammation and may reduce sickness or extreme fatigue in COVID‐19 patients 73 .…”
Section: Recent Findings On the Use Of The Trained Immunity‐based Vacmentioning
confidence: 96%
“…Recent studies have suggested that COVID-19 incidence and mortality rate is lower in countries where the BCG vaccine is a part of the routine childhood immunisation schedule. [22][23][24] The non-specific cross-protection against unrelated diseases is not limited to BCG and have also been described for other vaccines such as influenza.…”
Section: Pathology and Immunology Of Covid-19mentioning
confidence: 99%
See 2 more Smart Citations